Basic cartography for students and technicians : exercise manual - Anson, R. W.; Ormeling, Ferjan, 1942- (Published on behalf of the International Cartographic Association by Elsevier Applied Science, 1991)
Basic Cartography: For Students and Technicians; Exercise Manual.